Prospective Science Teachers’ Views on Socio-Scientific Issues: A Mathematical Modeling Study - Mısır, Muhammet Emin; İlhami, Aldeva (Journal of Natural Science and Integration, 2023)
The rapid changes in the world and the difficulties in accessing accurate information increase the need for individuals to engage in analytical and mathematical thinking. Therefore, educational reforms are being implemented, offering various approaches, including mathematical modeling. Mathematical modeling, which enables individuals to evaluate real-life situations using mathematical expressions, has recently been extensively studied in mathematical education but not science education. In this research, the topic of genetically modified organisms, a socio-scientific issue as a real-life situation, has been addressed. Sixteen prospective science teachers from a state university in the Marmara Region of Turkiye participated in the study. The “Genetically Modified Product Production” model eliciting activity developed by researchers was used as the data collection tool. The modeling activity aims to determine the prospective science teachers’ levels of mathematical modeling and their views on the production of genetically modified products. The data obtained from the research were analyzed using descriptive analysis methods. As a result of the research, although the participants encountered this activity for the first time, they generally demonstrated modeling competencies at Levels 2 and 3 (sufficient and moderate) in their solutions to the modeling activity. Regarding the production of genetically modified products, participants mainly expressed opposing views, considering it a socio-scientific issue.Keywords: socio-scientific issues, genetically modified organisms, mathematical modeling competencies